Synopsis of Religion and Child Abuse: The Nigerian Experience - Okebukola, Alexander Olufemi Afolabi (Mediterranean Journal of Social Sciences, 2012)
Child abuse is a common practice in Nigeria which should be minimized if not eradicated. Abuse, injustice,oppression, battery incidence and wickedness are prevalence against religious norms that teach wholeness,peace, liberty, emancipation and justice. It is against this background that the paper reviews the variouscomponents of child abuse, within this understanding, to examine the influence of religion on child abusein Nigeria. It then concludes with recommendations towards elimination of child abuse.